The Preconceptions of Economic Science - Veblen, Thorstein (Quarterly Journal of Economics, 1900)
Journal Article The Preconceptions of Economic Science Get access Thorstein Veblen Thorstein Veblen University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 14, Issue 2, February 1900, Pages 240–269, https://doi.org/10.2307/1883770 Published: 01 February 1900